Sequences of the Epstein-Barr Virus (EBV) large internal repeat form the center of a 16-kilobase-pair palindrome of EBV (P3HR-1) heterogeneous DNA. - Jenson, H B (1987)
We have previously characterized several genomic rearrangements of Epstein-Barr virus (EBV) DNA contained in one of the defective EBV genomes harbored by the P3HR-1 (HR-1) line (H. B. Jenson, M. S. Rabson, and G. Miller, J. Virol. 58:475-486, 1986). One recombinant clone of heterogeneous DNA (het DNA) from this defective genome is an EcoRI fragment of 16 kilobase pairs (kbp) which is a palindrome. DNA digestion fragments specific for the center of this palindrome were present in cells which contained het DNA but not in cells which lacked het DNA. Thus, the palindrome was not an artifact of DNA cloning. The organization of the center of this palindrome was studied by DNA sequencing. The comparable region of the parental HR-1 genome was also studied by DNA sequencing. The central 3,495 base pairs (bp) of the palindrome were composed of sequences derived exclusively from internal repeat 1 of EBV, represented by BamHI W fragment. At each end of the central 3,495 hp was a symmetrical recombination with sequences of BamHI-Z, located more than 50 kbp away on the standard EBV genome. The central 3,495 bp were composed of an unduplicated 341 bp flanked by two perfect palindromic repeats of 1,577 bp. The 341-bp unique region was a portion of a 387-bp region of standard HR-1 BamHI-W which was identical to the central 387 bp of the palindrome. This central 387-bp region contained numerous stretches of dyad symmetry capable of forming a large stem-and-loop structure. The palindromic rearrangement had created two novel open reading frames in het DNA derived from standard HR-1 BamHI-W sequences. These two het DNA open reading frames had different amino termini but identical carboxy termini derived from the large open reading frame in standard HR-1 BamHI-W (HR-1 BWRF1). The BamHI-W sequences found in het DNA did not include either the TATA box of standard HR-1 BamHI-W or the exons which are present in the potentially polycistronic latent mRNAs encoding EBV nuclear antigens. These marked alterations in genomic structure may relate to the unique biologic properties of virus stocks containing het DNA by creation of new polypeptides or by formation or deletion of regulatory or functional signals.